Liver disease in cystic fibrosis - Kobelska-Dubiel, Natalia; Klincewicz, Beata; Cichy, Wojciech (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Cystic fibrosis-associated liver disease (CFLD) affects ca. 30% of patients. The CFLD is now considered the third cause of death, after lung disease and transplantation complications, in CF patients. Diagnostics, clinical assessment and treatment of CFLD have become a real challenge since a striking increase of life expectancy in CF patients has recently been observed. There is no elaborated “gold standard” in the diagnostic process of CFLD; clinical evaluation, laboratory tests, ultrasonography and liver biopsy are used. Clinical forms of CFLD are elevation of serum liver enzymes, hepatic steatosis, focal biliary cirrhosis, multilobular biliary cirrhosis, neonatal cholestasis, cholelithiasis, cholecystitis and micro-gallbladder. In children, CFLD symptoms mostly occur in puberty. Clinical symptoms appear late, when damage of the hepatobiliary system is already advanced. The CFLD is more common in patients with severe mutations of CFTR gene, in whom a complete loss of CFTR protein function is observed. CFLD, together with exocrine pancreatic insufficiency and meconium ileus, is considered a component of the severe CF phenotype. Treatment of CFLD should be complex and conducted by a multispecialist team (gastroenterologist, hepatologist, dietician, radiologist, surgeon). The main aim of the treatment is to prevent liver damage and complications associated with portal hypertension and liver cirrhosis. Ursodeoxycholic acid is used in the treatment of CFLD. There is no treatment of proven long-term efficacy in CFLD. Liver transplantation is a treatment of choice in end-stage liver disease.